‘NOUVEAU INFORMATION POOR’ DALAM PERADABAN GELOMBANG KETIGA (Fenomena Masyarakat Miskin Informasi di Kawasan Timur Indonesia) - Hikmah Tahir (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2013)
Advances in information technology is characterized by its characteristics by socioeconomic status will always be a difficult problem solved. System formed then divided between those who are able to adopt the technology that can not afford as a result of the presence of this innovation. Related to the gap in the information society, Green (2002) termed nouveau riche information for people who get sudden access to ICTs eg through promotion, becoming student) and nouveau poor information and people who lose access to ICTs as a result of poverty or sudden change in circumstances life eg unemployment. To overcome this problem in eastern Indonesia, the Indonesian government has made several programs, among other programs Warung Indonesia Information and Cyber Village establishment. However, these programs are still experiencing a lot of problems, mainly related to infrastructure in the region is still minimal.